An Economic Analysis of Delayed Primary School Enrollment in a Low Income Country: The Role of Early Childhood Nutrition - Glewwe, Paul; Jacoby, Hanan G. (The Review of Economics and Statistics, 1995)
Paul Glewwe, Hanan G. Jacoby, An Economic Analysis of Delayed Primary School Enrollment in a Low Income Country: The Role of Early Childhood Nutrition, The Review of Economics and Statistics, Vol. 77, No. 1 (Feb., 1995), pp. 156-169